Sustaining village malaria worker programmes with expanded roles: Perspectives of communities, healthcare workers, policymakers, and implementers in Vietnam - Nguyen, H; Jongdeepaisal, M; Tuan, DA; Khonputsa, P; Ngo, T; Pell, C; Liverani, M; Maude, RJ (Public Library of Science, 2024)
Background: In Vietnam, multiple types of community-based malaria workers are recruited to promote access to malaria testing and treatment for at-risk mobile and migrant populations. However, as the country approaches elimination, these roles are at risk from declining investment. This article characterises the different types of workers and relevant health policy in Vietnam, and explores stakeholder perspectives on sustaining and expanding the roles of these workers in the malaria elimination context. Methods: We conducted a rapid policy document review to describe the policy background of community-based health care in Vietnam and identify key informants. In-depth interviews were conducted with policymakers and implementers (n = 11) in different government sectors, international, and civil society organizations. We also conducted interviews (n = 8) and two focus group discussions with community members (n = 12), and interviews with health workers (n = 9) in 18 communities in Phu Yen and Binh Thuan provinces in the central region. Results: Our study identified three main types of malaria workers: village health workers (VHWs), malaria post workers (MPWs) and other groups of workers supported by civil society organisations (CSO). Workers reported being willing to maintain their current roles and potentially provide additional services that respond to community needs, although they were concerned about excess workload and inadequate income. Besides working in a variety of jobs to secure their incomes, mainly in agriculture, VHWs in particular were primarily tasked with supporting the delivery of a wide range of health services from commune health stations. Faced with reduced patients, MPWs and CSO-supported workers could be tasked with the following potential roles: case notification for infectious diseases, real-time data collection and reporting, and screening for non-malaria illnesses using other rapid test kits. There was agreement that the community-based health network is crucial to health care delivery in remote communities and to ensure comprehensive access to care among vulnerable populations. However, policymakers and implementers stressed concerns about their limited skillsets, the inadequate budget to support these workers, and the regulation constraining them from performing diagnosis and treatment activities, highlighting the priority to maintain the capacity of workers and funding allocation through provincial advocacy and multi-programme collaboration. Conclusions: This study highlights the crucial role of community-based health workers in eliminating malaria in Vietnam. Sustained efforts are needed to maintain accessible case detection and treatment while addressing local health concerns beyond malaria. Implementing these strategies requires prioritizing the mapping of groups most in need and developing enablers to raise community awareness and maintain the capacity of these workers. Ensuring political advocacy, financial resources, and coordination between multiple groups are key to maximizing impact and integrating malaria activities into the broader health system.